Pengetahuan dan Sikap Pasangan Suami Istri mengenai masalah Kesehatan Reproduksi Perempuan Hubungannya dengan Partisipasi Pria dalam Keluarga Berencana - Aman Widodo, Siswanto Agus Wilopo,Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Problem of gender equality and men responsibility in relationship with reproduction problem and family planning is a new paradigm of family planning program that established from Kairo Agreement in 1994. One of the obstacles in improving men participation in family planning is community's incorrect attitude that tends to consider women as the target of reproduction problem. Incorrect attitude occurred as the result of lack of family knowledge regarding problem of women reproduction health.Objectives: This research was aimed to know the description of socio-demography characteristic, knowledge and attitude of husband and wife regarding problem of women reproduction health. Also, this research was aimed to investigate the relationship between socio-demography characteristic, knowledge and attitude of husband and wife regarding women reproduction health problem with men participation in Family Planning.Methods: This non-experimental research with cross sectional design was done in Brebes regency. The subjects were couples who had, minimum, 1 child, and still using contraception. The sample was taken with simple random method. Chi square and logistic regression were used for data analysis. Results and conclusions: The result of this research showed that socio-demography (income and place of service), knowledge of family regarding women reproduction health problem, and attitude of family regarding women reproduction health problem, were factors that had relationship with men participation in family planning (p0,05). Keywords: Socio-demography characteristic, knowledge, attitude, reproduction health, and men participation in family planning.